An Analysis of Thematic Progression in the Novel “The Wicked King” by Holly Black - I Gusti Ngurah Pedi Pradjana; I Gusti Ayu Vina Widiadnya Putri (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2024)
The study focuses mainly on the thematic and thematic development patterns observed in The Wicked King Novel. This study employs qualitative techniques and descriptive designs to test the data. The information was provided by renowned novelist Holly Black. Thematic development patterns were examined utilizing Paltridge theory (2006), Rheme theory (2004), and Halliday theory (2004) in the evaluation of the data. The study indicated that the Reiterated/Constant Theme Pattern was the most prevalent in thematic progression patterns, with Participant being the most dominant Topical Theme in the Thematic Progression type. Based on the outcome, it was found that topical theme as participant is 9 sentences, topical theme as circumstance is 8 sentences, and topical theme as process is 4 sentences, so the total of topical theme is 21 sentences (65, 5%), textual theme with 5 sentences (15, 6%), and interpersonal theme with 6 sentences (18, 17%). So, based on the data, topical themes are the most common.